The sources of interindustry wage differentials - Priscila Ferreira (University of Essex, Institute for Social and Economic Research (ISER), 2009)
We analyse the nature of interindustry wage differentials using Portuguese data. Es- timates from models controlling for observed worker and firm characteristics reveal sig- nificant and persistent raw interindustry dierentials, which questions the competitive model of the labour market. However, estimates controlling for unobserved worker het- erogeneity suggest that the raw dierentials are due to the concentration of high wage workers in certain industries and not to genuine dierences in compensation across industries. However, a complete decomposition shows that (i) firm effects on average explain 70% of the industry wage premia, and (ii) genuine and sizeable interindustry wage differentials exist. These dierentials are shown to increase the time to separation from firms, and are therefore compatible with the competitive model.
Keywords: 330